Prognostic nomogram for patients with advanced unresectable hepatocellular carcinoma treated with TAE combined with HAIC - Du, Li-xin; Sheng, Guo-li; Shi, An-da; Li, Kang-shuai; Liu, Zeng-li; Tang, Yong-chang; Liu, Yi; Zhang, Zong-li (Frontiers in Pharmacology, 2024)
Abstract Background: Hepatocellular carcinoma (HCC) is the most common primary liver cancer and often arises in the context of chronic liver disease, such as hepatitis B or C infection, and cirrhosis. Advanced unresectable HCC (uHCC) presents significant treatment challenges due to its advanced stage and inoperability. One efficient treatment method for advanced uHCC is the use of hepatic arterial infusion chemotherapy (HAIC) combined with transcatheter arterial embolization (TAE). Patients and methods: In this study, we conducted a retrospective collection of clinical data, including basic information, radiological data, and blood test parameters, for patients with advanced uHCC who underwent TAE+HAIC treatment from August 2020 to February 2023. A total of 743 cases involving 262 patients were included. Ultimately, the covariates included in the analysis were the Child-Pugh score, extrahepatic metastasis, tumor number, tumor size, and treatment method. Results: In the study, we performed univariable and multivariable analysis on 23 clinical factors that were screened by LASSO regression, indicating that the 5 variables aforementionedly were identified as independent factors influencing patient prognosis. Then we developed a nomogram of the sensitive model and calculated concordance indices of prognostic survival models. Conclusions: Based on the uHCC patient cohort, we have developed a prognostic model for OS in patients who received TAE+HAIC treatment. This model can accurately predict OS and has the potential to assist in personalized clinical decision-making. Key words: unresectable hepatocellular carcinoma; HAIC; TAE; survival analysis; prognostic model